A Speech Act Analysis of Non-Standard English Uttered by the Main Character of 8 Mile Movie - Agistiawati, Eva (IJOSMAS, 2023)
The non-standard variety of the English language is often referred to as uneducated or unintelligent people who come from the lower-class and lower working class. Therefore, the differences in people’s social background will influence the choice of language use in societies. The objectives of the study are to identify the functions of the illocutionary acts spoken by the main character of 8 Mile and to describe the effects of the speech acts used by the main character toward the hearer’s behavior. This research is designed as descriptive qualitative research. The object is the film script of 8 Mile. There are 92 scenes in the 8 Mile film script and a sample of 47 scenes was conducted using a purposive sample technique. As many as 110 of the main character’s utterances of 8 Mile were gathered and treated as the data of this research. The instruments were the researcher herself, helped by the data sheets and several selected relevant guiding books. To gain the validity of the research, the researcher used a triangulation technique by consulting the data with her consultants, asking some of her friends in the English Literature Study Program, and also repeating the observations several times. The findings reveal four functions of the illocutionary acts spoken by the main character of 8 Mile and ten perlocutionary acts used by the main character toward the hearer’s behavior in 8 Mile. The functions of the illocutionary acts are assertive (33.69%), directives (43.70%), commissive (4.08%), and expressive (18.52%). The perlocutionary acts are to convince the hearer (20.59%), to surprise the hearer (4.41%), to bore the hearer (1.96%), to annoy the hearer (1.96%), to frighten the hearer (2.46%), to cause the hearer (33.82%), to insult the hearer (2.94%), to alarm the hearer (0.49%), to make the hearer do something (9.80%), and to make the hearer realize something (21.56%).